Function and regulation of cholecystokinin octapeptide, β-endorp hin and gastrin in anorexic infantile rats treated with ErBao Granules - Du, Yong-Ping (World J Gastroenterol, 2001)
AIM: To study the role of cholecystokinin octapeptide (CCK-8), β-endorphin (β-EP), and gastrin in an anorexic infantile rat model and no subsequent regulation of nose peptides by the Yunpi complex prescription ErBao Granule. METHODS: We fed infantile rats with special prepared forage. A liquid extract of ErBao Granule was administered to the rats daily for 3 weeks, CCK-8, β-EP, and gastrin concentrations in hypothalamus, gastric antrum, and plasma of the rats were measured by radioimmunoassay, and were compared with controls. RESULTS: Treatment of rats with ErBao Granule inhibited CCK-8 secretion and increased β-EP and gastrin secretion. CCK-8 concentration in hypothalamus and plasma of model control group increased significantly and correlated negatively with food intake of models, respectively. β-EP concentration in gastric antrum and plasma of model control group decreased significantly and showed a positive correlation with food intake of models, respectively. Hypothalamus concentration of β-EP was similar in models and controls. Gastrin concentration in gastric antrum of models was lower than in the blank control group, and correlated positively to food intake of models. Finally, CCK-8 concentrations in plasma of rats showed a positive correlation with plasma β-EP (r = -0.68, P < 0.05). CONCLUSION: The increased plasma and hypothalamus concentration of CCK-8, decreased gastric antrum and plasma level of β-EP, and decreased gastric antrum concentration of gastrin are associated significantly with the anorexia of infantile anorexic rat models produced by special forage. ErBao Granule can reverse these changes, which may be the major mechanisms of ErBao Granule simulating feeding.